การลดปริมาณขยะขวดพลาสติก PET โดยการตั้งโรงงานผลิตเม็ดพลาสติกรีไซเคิล - กนิษฐา นาคประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research studies the cost of the recycling plant for PET bottle waste which is estimated for Thailand (Bangkok, municipality and Pattaya) from 2010 to 2024. Long-run marginal cost analysis through an average incremental cost (AIC) at constant price (2009) in different quantity and minimum AIC analysis were conducted, which yielded optimum price for recycled PET and polyester’s manufacturers. This research also compares AIC with the market price of recycled PET and virgin PET resin in order to evaluate an ability to sell recycled PET for polyester’s manufacturers. The results show that the optimum quantity at minimum AIC is 8,000 ton/year, with the unit cost is 21.80 Baht/Kg. and the AIC is 23.78 Baht/Kg, which can make the profit 1.98 Baht/Kg. The AIC is lower than the market price of recycled PET (24-26 Baht/Kg.) and virgin PET resin (35-44 Baht/Kg.). The manufacturers can attract polyester’s manufacturers to use recycled PET as raw material in an appropriate ratio instead of using only virgin PET resin. To summarize, the recycling plant is considered as an efficient investment to help reducing PET bottle waste.